(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Acute laryngitis is a prevalent condition in children and holds a significant place among respiratory tract illnesses. This illness is primarily characterized by inflammation of the vocal cords and the mucous membrane of the larynx (voice box). Key signs of acute laryngitis include the development of a barking cough, changes in voice (particularly hoarseness), and difficulty breathing. In many cases, this condition develops in children against the backdrop of a viral infection, though other factors can also contribute to the onset of the disease.